PSYCHOLOGICAL MECHANISMS OF CRITICAL THINKING DEVELOPMENT IN THE MODERN EDUCATIONAL PROCESS (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the formation of critical thinking competencies in an individual in the modern education system in the context of globalization and the expansion of the digital information space, the interpretation of critical thinking in pedagogical psychology as an integrative process representing a high level of cognitive activity of the individual, its connection with a purposefully organized educational environment and psychological mechanisms, questions and answers and discussion, problem-based learning, reflection, communication and cooperation, as well as psychological mechanisms based on simulation and role-playing, metacognitive control, analytical and reflexive thinking, and the problems of these mechanisms in students